2008
DOI: 10.1080/14786410701869341
|View full text |Cite
|
Sign up to set email alerts
|

A new dihydrochalcone from dragon's blood, red resin ofDracaena cochinchinensis

Abstract: A new dihydrochalcone, 4'-hydroxy-4,2'-dimethoxy-dihydrochalcone, was isolated from Chinese dragon's blood, the red resin of Dracaena cochinchinensis. Its structure was established by spectrum analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The structures and sources of 15 new mono-C-glycosylflavones (383)(384)(385)(386)(387)(388)(389)(390)(391)(392)(393)(394)(395)(396)(397) published in the 2007-2009 period are listed in Table 3. 38,259, A 6-C-b-glucopyranoside (383) of the relatively simple flavone, chrysin 7-methyl ether (5-hydroxy-7-methoxyflavone) has been isolated from extracts of the aerial parts of the aromatic herb, Sphaeranthus indicus (Asteraceae), which is well known as a medicinal plant in India.…”
Section: Mono-c-glycosylflavonesmentioning
confidence: 99%
“…The structures and sources of 15 new mono-C-glycosylflavones (383)(384)(385)(386)(387)(388)(389)(390)(391)(392)(393)(394)(395)(396)(397) published in the 2007-2009 period are listed in Table 3. 38,259, A 6-C-b-glucopyranoside (383) of the relatively simple flavone, chrysin 7-methyl ether (5-hydroxy-7-methoxyflavone) has been isolated from extracts of the aerial parts of the aromatic herb, Sphaeranthus indicus (Asteraceae), which is well known as a medicinal plant in India.…”
Section: Mono-c-glycosylflavonesmentioning
confidence: 99%
“…3 Previous studies showed that the resin contains mainly of phenolic compounds, as well as several steroids and aliphatic acids. [30][31][32][33][34][35][36][37][38] In our continuing studies on Chinese dragon's blood, five new flavonoid oligomers namely cochinchinenins D-H (1-5) were further isolated and identified from the red resin of D. cochinchinesis, in addition to the known biflavonoid, cinnabarone (6), and a mixture of two known biflavonoids, socotrin-4'-ol (7) and homoisosocotrin-4'-ol (8). Their structures were elucidated on the basis of detailed spectroscopic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Flavans (Figure 10): 7,4'-dihydroxy-8-methylflavan (45) [43,44,49], 4,4′-dihydroxy-2,6dimethoxydihydrochalcone [47,48], (2R)-7,4'-dihydroxy-5-methoxy-8-methylflavan [49], 5,4'dihydroxy-7-methoxy-6-methylflavan (46) [44,46,49], 7,4'-dihydroxy-3'-methoxyflavan [49], 7,4'dihydroxyflavan (47) [46,49], (-)-7-hydroxy-4′-methoxyflavan [43,[45][46][47], (2S)-7,4′-dihydroxy-8methylflavan (48) [46,47], (2S)-5,4′-dihydroxy-7-methoxy-8-methylflavan [47], (2R)-4′-hydroxy-7methoxy-8-methylflavan [47], and 6,4'-dihydroxy-7-methoxy-8-methylflavan [46]. Homoisoflavans and meta-homoisoflavans (Figure 11): (3R)-7,4′-dihydroxy-5,8-dimethoxyhomoisoflavan [(3R)-dracaeconolide B] (49) [49] (Figure 11) (3R)-7,4'-dihydroxy-8-methoxyhomoisoflavan (50) [48,49,53], (3R)-7,4′-dihydroxyhomoisoflavan (51) [45,46,48,49], (3R)-7,4'dihydroxy-5-methoxyhomoisoflavan (52) [42,46,48,49], 7,4'-dihydroxyhomoisoflavan (53) [43,44], (3R)-7,4′-dihydroxy-6-methoxyhomoisoflavan [52], 6,4'-dihydroxy-7-methoxyhomoisoflavan (54) [43,…”
Section: Dracaena Cochinchinensis (Lour) Sc Chenmentioning
confidence: 99%
“…homoisoflavan (50) [48,49,53], (3R)-7,4′-dihydroxyhomoisoflavan (51) [45,46,48,49], (3R)-7,4'dihydroxy-5-methoxyhomoisoflavan (52) [42,46,48,49], 7,4'-dihydroxyhomoisoflavan (53) [43,44], (3R)-7,4′-dihydroxy-6-methoxyhomoisoflavan [52], 6,4'-dihydroxy-7-methoxyhomoisoflavan (54) [43,46], (3R)-6,4'-dihydroxy-8-methoxyhomoisoflavan [49], 7,3′-dihydroxy-8,4′-dimethoxyhomoisoflavan [48], 4′-hydroxy-7,8-dimethoxyhomoisoflavan [48], 4′-hydroxy-5,7-dimethoxyhomoisoflavan [48], (7R,12bR)-7,10-dihydroxy-4,11-dimethoxydracaenone (55) [52], (7S,12bS)-11-hydroxy-1,10-dimethoxydracaenone (56) [52], (7S,12bS)-10,11-dihydroxy-1-methoxydracaenone (57) [52], 10hydroxy-11-methoxydracaenone (58) [52], 10,11-dihydroxydracaenone C (59) [44], and 4'-hydroxy-7,8-methylenedioxyhomoisoflavan (23) [46,48]. Flavonoid dimers and trimers (Figures 12 and 13): cochinchinenenes A-D (structures 60,63-65 in Figure 11) [44,47,53], cochinchinenenes E (66) and F (61) [43], cochinchinenenes G (67) and H (62) [44], "cochinchinenene G" (68) [42], (2R)-8-methylsocotrin-4′-ol (69) [47], cochinchinenin [44], cochinchinenin B (75 [44,47]…”
Section: Dracaena Cochinchinensis (Lour) Sc Chenmentioning
confidence: 99%